USP3 inhibition is Active Against Chemo-resistant Hepatocellular Carcinoma Anchorage-independent Growth via Suppressing Wnt/β-catenin - Xu, Jianguo; Gui, Ge Sang Wang; Yang, Chao; Zhu, Shuchen; Chen, Zemin; Ma, Suo Lang Bai; Yang, Ci; Bu, Ci Ren Luo; Zhu, Ying; Xu, Wen (Current Molecular Medicine, 2024)
Background: USPs are a family of enzymes that regulate protein degradation, and their dysregulation has been implicated in the development and progression of cancer. Aims: This study aimed to determine whether ubiquitin-specific proteases 3 (USP3) could be a potential target for therapy in hepatocellular carcinoma (HCC), particularly in resistant HCC. This study systematically investigated the role of USP3 in HCC, with a focus on chemo-resistant HCC cells. Methods: The level of USP3 from clinical samples was measured using an ELISA assay. Cell proliferation, apoptosis, migration, and anchorage-independent colony formation assays were performed. Transfection was performed to knock down USP3 expression and measure β-catenin activity, and real-time PCR was used to measure levels of MYC and CYCLIN D1 genes. Results: USP3 protein was upregulated in HCC tissues, but its upregulation was not associated with clinicopathology. USP3 knockdown had a similar inhibitory effect on growth in both sensitive and resistant HCC cells, did not affect migration, and induced apoptosis in sensitive but not resistant HCC cells. Furthermore, USP3 knockdown was more effective in suppressing anchorage-independent colony formation in chemoresistant HCC cells compared to their chemo-sensitive counterparts. Pearson correlation coefficient analysis revealed a strong positive correlation between USP3 and CTNNB1, and consistently, USP3 knockdown reduced the levels and activities of β-catenin in HCC cells. Using a Wnt activator (lithium) in rescue studies significantly reversed the inhibitory effects of USP3 knockdown. Conclusion: The findings suggest that inhibiting USP3 is an effective strategy against cancer stem cells and chemo-resistant HCC cells.
Keywords: sensitizing target